The development process of intrinsic gamification in a learning difficulty context - Liu Liu; Patrick Stacey (2015)
The paper explores the development process of intrinsic gamification in a learning difficulty context through an in-depth case study. We found out that simplicity is the most vital mechanic and the freedom in the software benefits users physically, mentally and socially. As a result, the software meets user’s competence, autonomy and connection needs and thus intrinsically motivates them to use it more.